2016
DOI: 10.1016/j.jvs.2016.03.427
|View full text |Cite
|
Sign up to set email alerts
|

Improving mortality trends for hospitalization of aortic dissection in the National Inpatient Sample

Abstract: Overall and surgical admission rates for AD appear to be increasing, and in-hospital mortality rates are decreasing. TEVAR mortality remains mostly unchanged, however, suggesting targets for further improvement in mortality for AD treatment. Decreased mortality for TBSR at centers with a high surgical volume may suggest a need for regionalization of AD care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 30 publications
3
29
0
1
Order By: Relevance
“…It is clear that at least some of the impact on improving survival is related to these factors (18, 19). The overall operative mortality rate of 18.9% in this cohort, is consistent with the current literature (69, 1618, 2022). Mody et al demonstrated significant improvement in 30-day mortality for Medicare patients from 30.7% in 2000 to 21.4% in 2011, similar to an IRAD analysis where in-hospital mortality decreased from 25.0% in an era starting in 1996 to 18.4% currently (7, 8).…”
Section: Commentsupporting
confidence: 92%
See 1 more Smart Citation
“…It is clear that at least some of the impact on improving survival is related to these factors (18, 19). The overall operative mortality rate of 18.9% in this cohort, is consistent with the current literature (69, 1618, 2022). Mody et al demonstrated significant improvement in 30-day mortality for Medicare patients from 30.7% in 2000 to 21.4% in 2011, similar to an IRAD analysis where in-hospital mortality decreased from 25.0% in an era starting in 1996 to 18.4% currently (7, 8).…”
Section: Commentsupporting
confidence: 92%
“…Many centers of excellence report improved rates of survival in patients undergoing surgical repair of TAAD over the past two decades (6, 7). These improvements have been due to an evolution in approaches, cannulation strategies, cerebral perfusion, and temperature management (810).…”
mentioning
confidence: 99%
“…First, owing the emergent nature of AAS, no randomized trials of abdominal aortic aneurysm interventions were retrieved, therefore limiting our qualitative and quantitative analysis to retrospective observational studies only, often with a limited sample size. 2150 Retrospective studies are subject to confounders and bias, possibly resulting in a decline in the power of our meta-analysis. The majority of collected data were derived from a simple univariate comparison analysis, therefore limiting the opportunity to perform sub-group analysis, especially with reference to the different entities included in the wide definition of AAS.…”
Section: Limitationsmentioning
confidence: 99%
“…Com uma apresentação clínica que abrange desde o indolente e provavelmente benigno (pequeno aneurisma aórtico) ao emergente e com risco de vida (dissecção aórtica). Por isso, a alocação adequada de recursos de serviços de saúde para garantir atendimento de qualidade ao paciente torna-se um desafio (MODY et al, 2014;PAPE et al, 2015;ZIMMERMAN et al, 2016).…”
Section: Introductionunclassified